Dielectric and piezoelectric properties of the mechanochemically prepared PZT ceramics - Brankovic, Z.; Brankovic, G.; Moura, F.; Varela, José Arana [UNESP] (Kluwer Academic Publ, 2004)
Mechanochemical synthesis was applied to obtain nanocrystalline powders of composition Pb(Zr0.52Ti0.48)O-3 (PZT). Milling was performed in a planetary ball mill using vials and balls made of zirconia or steel-in order to investigate influence of milling media on the electrical properties of resulting ceramics. PZT ceramics showed high values for dielectric constant (epsilon(r)), reaching 970 at room temperature, as well as low dielectric loss (tandelta) under the optimal processing conditions. High values of remanent polarization (P-r) indicate high internal polarizability. The best samples showed piezoelectric strain constant d(33) = 347 pC/N and planar coupling factor k(P) = 0.44. Milling in ZrO2 medium prevents powder contamination and provides reproducibility of milling process. Also, PZT obtained from the powders milled in ZrO2 exhibited lower values of dielectric loss, in comparison with the PTZ obtained from the powders milled in Fe. This suggests that contamination of the powder with Fe could result in an increase of conductivity in final product. (C) 2004 Kluwer Academic Publishers.